Gender asymmetries: Impacts of an early-stage school intervention in the Philippines - Yamauchi, Futoshi; Liu, Yanyan (John Wiley & Sons, 2018)
This paper examines long‐term impacts of improved school quality at the elementary school cycle on subsequent schooling investments and labor market outcomes using unique data from a survey that tracked nearly 3,500 former students in the Philippines. The Third Elementary Education Project (TEEP) intervention introduced a package of investments and management reforms at the school level, including classroom constructions, textbooks, teacher training, and school‐based management in the period of 2000 to 2006. The impacts on subsequent schooling investments and labor market earnings differ between females and males. The intervention significantly increased earnings among females, which reduced the existing wage gap by gender. However, the findings on schooling outcomes are mixed; the gender gap tended to widen, enhancing females’ existing relative advantage in schooling, though their impacts are insignificant for both females and males.